Current-Transformer Saturation Reconstruction Using a Normalized Least Mean Squares Adaptive Method - Saremi, Amin; Mohammadi, Younes; Khodadad, Davood; Polajžer, Boštjan (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper proposes a computationally light adaptive-filtering approach, normalized least mean squares (NLMS), to model the nonlinearity caused by the current transformer (CT) iron core saturation. A simplified CT model was used to generate a dataset considering four different nonlinear iron core magnetic characteristics. The preliminary results show satisfactory results in the cases where the CT iron core nonlinearity is within certain limits.